Anesthetic experimental device for small animal - Vivas,Luiz Alfredo de Magalhães (2007)
PURPOSE: The difficulty to anesthetize small laboratory animals with vaporizer prompted us to go in search of new materials, and create new techniques. The improved equipment of anesthesia we looked for should be low cost, practical, versatile, and its management serve ethical, teaching, and research purposes. METHODS: The new components of the equipment were: the vaporizer, the unidirectional valve, the glass cylinder filled with water, the flow guidance y-shape tube, the flow regulators, the mask modifications, and another free airway for emergency occurrence. A test was done with 30 Wistar rats, Rattus norvegicus albinus, divided into three groups with 10 rats for each one. Groups 1, 2 and 3 were anesthetized with Ether, Halothane and Sevoflurane respectively, using the new gadget. The anesthetic induction time, the breathing rhythm alteration during an anesthesia pre-established time (10 minutes), and the recovery time were observed. RESULTS: The equipment enabled an easy handling, and fulfilled a larger safeness and stability during the induction and anesthetic management. The test showed it was possible to make use of several anesthetic agents. CONCLUSION: The device is effective, and turns the anesthesia procedure into a very easy practice with low-cost. It should be recommended for experimental surgery, teaching and research.